2022
DOI: 10.1108/jaee-06-2021-0207
|View full text |Cite
|
Sign up to set email alerts
|

Impact of board attributes on stock liquidity: evidence from Pakistani panel data

Abstract: PurposeThis study investigates the impact of board characteristics on the stock liquidity of Pakistani listed non-financial firms for the period 2007–2016.Design/methodology/approachThe study uses fixed-effects regression model on a sample of 170 non-financial firms listed on the Pakistan Stock Exchange for regressing the impact of board attributes on stock liquidity while for addressing the endogeneity two-stage least-square (2SLS) and lagged structure models are used.FindingsThe study finds that board meetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Empirically, they showed that more frequent board meetings are related to higher stock liquidity. Khan et al (2022) also found that board meeting frequency is positively and significantly associated with stock market liquidity. Based on the arguments above, the following hypothesis is developed: H3: Frequent board meetings improves stock liquidity.…”
Section: Board Meetings and Stock Market Liquiditymentioning
confidence: 84%
See 1 more Smart Citation
“…Empirically, they showed that more frequent board meetings are related to higher stock liquidity. Khan et al (2022) also found that board meeting frequency is positively and significantly associated with stock market liquidity. Based on the arguments above, the following hypothesis is developed: H3: Frequent board meetings improves stock liquidity.…”
Section: Board Meetings and Stock Market Liquiditymentioning
confidence: 84%
“…They emphasized that this positive relationship becomes stronger if firms have poor governance. Khan, Rehman, and Khan (2022) investigated the effect of board composition on the stock market liquidity of non-financial Pakistani firms from 2007 to 2016. They found that directors' attendance, frequency of board meetings, the number of board sub-committees and board gender diversity positively influenced stock market liquidity.…”
Section: Review Of Board Structure and Stock Market Liquidity Studiesmentioning
confidence: 99%
“…of these attempts demonstrated a positive effect of GD on SL; furthermore, they proved that the positive impact of GD on SL became stronger with the higher presence of females (e.g., Ahmed and Ali, 2017;Loukil et al, 2019;Nguyen and Muniand, 2021;Ye et al, 2021;Abidi and Nsaibi, 2022;Khan et al, 2022). The positive effect of GD on SL may be a result of investors' confidence in women to add value and improve the interests of shareholders (Sudeck and Latridis, 2014).…”
Section: The Moderating Impact Of Gender Diversity On Income Smoothin...mentioning
confidence: 98%
“…The dependent variable in the current study is SL. Most prior studies employed the Amihud illiquidity measure (2002) to estimate SL (e.g., Bazrafshan et al, 2021;Khan et al, 2022;Abidi and Nsaibi, 2022;Michael et al, 2022) because it is strongly associated with the high-frequency price impact benchmark, allows a better understanding of liquidity premium, and the simplicity of its construction (Lou and Shu, 2017). This measure can be illustrated by the ratio of the absolute stock return to the trading volume of the stock as follows (Amihud, 2002): Where ILLIQiy refers to the value of stock illiquidity for a firm (i), on a day (d), and a year (y).…”
Section: Variables Descriptionmentioning
confidence: 99%
See 1 more Smart Citation